Effect of nasal obstruction surgery on eustachian tube function and middle ear ventilation - Rathaur, Shiv Kumar; Verma, Jagram (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: The purpose of this study was to assess the effect of surgery for nasal obstruction in improving Eustachian tube function and middle ear ventilation. Methods: This prospective study involved 60 patients with different nasal pathologies causing nasal obstruction along with complaints of ear fullness. In required cases the nasal pathologies were surgically managed. Pre and postoperative impedance audiometric evaluation and nasal endoscopy were done to assess the eustachian tube function, changes the value of middle ear pressure and ear fullness sensation at 1 month and at 3 months after surgery. Results: Preoperatively, 56 (93.3%) patients had sensation of ear fullness, postoperatively at 1 month and at 3 months after nasal surgery only 20 (33.3%) patient and 18 (30%) respectively, has sensation of ear fullness, with signiﬁcant improvement (p<0.05). Preoperatively, 74 (61.6%) ears were type A tympanogram, 50 ears of them had poor eustachian tube function and 24 ears had good Eustachian tube function. 42 (35%) ears were type C, 4 (3.3%) ear were type B tympanogram, all of them had poor eustachian tube function. The postoperative results of eustachian tube function test and tympanometric value were signiﬁcantly better than preoperative results (p<0.05). Conclusions: We find out that nasal obstruction has a deﬁnite relationship with eustachian tube function. Surgery for nasal obstruction has a favourable effect on the middle ear pressure and eustachian tube function. Corrective surgery for nasal obstruction should be considered at least 1 month before undertaking the middle ear surgery to improve middle ear ventilation.